2010
DOI: 10.1071/rd10013
|View full text |Cite
|
Sign up to set email alerts
|

Survival and apoptosis rates after vitrification in cryotop devices of in vitro-produced calf and cow blastocysts at different developmental stages

Abstract: Two experiments were designed to determine the ability of in vitro-cultured blastocysts at different stages of development to survive the vitrification procedure using cryotop devices. Day 7 and Day 8 embryos were classified as non-expanded, expanded or hatching and/or hatched blastocysts. In the first experiment, we examined the survival rate of vitrified-warmed blastocysts after 3 h incubation in synthetic oviducal fluid (SOF) medium. In the second experiment, vitrified-warmed blastocysts were evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 35 publications
8
31
3
3
Order By: Relevance
“…In a previous study, in which the embryos were not exposed to CLA, our group observed a distinct behavior after vitrification of the embryos at the same stage, but cryopreservation at D7 or D8 (MEZZALIRA et al, 2004). In this study, embryos at an early developmental stage (BLs) were less cryotolerant than those at a later developmental stage (EBs), similar to what was reported by Morató et al (2010). During BL formation and expansion, lipids are metabolized by the trophoblastic cells, which may explain the increased cryotolerance of EBs compared to the BL-stage IVP bovine embryos.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In a previous study, in which the embryos were not exposed to CLA, our group observed a distinct behavior after vitrification of the embryos at the same stage, but cryopreservation at D7 or D8 (MEZZALIRA et al, 2004). In this study, embryos at an early developmental stage (BLs) were less cryotolerant than those at a later developmental stage (EBs), similar to what was reported by Morató et al (2010). During BL formation and expansion, lipids are metabolized by the trophoblastic cells, which may explain the increased cryotolerance of EBs compared to the BL-stage IVP bovine embryos.…”
Section: Discussionsupporting
confidence: 75%
“…This is possible by embryo culture in serum-free systems (ORDOÑEZ-LEON et al, 2014) or by mechanical removal of intracellular lipids (KAWAKAMI et al, 2008). However, both approaches reduce the developmental viability of embryos.…”
Section: Introductionmentioning
confidence: 99%
“…This damage may occur due to the use of high concentrations of cryoprotectant solutions employed in the current vitrification technique to generate a glass-like physical state (Campos-Chillòn et al, 2006), which increases the risk of osmotic and toxic damage (Barceló-Fimbres & Seidel, 2007b). Conversely, Morató et al (2010) did not observe any difference in apoptosis rates between fresh and vitrified blastocysts. However, the authors justify that the period between warming and DNA fragmentation examination (3 h) was not enough to identify the extention of damage caused by the vitrification-warming procedure.…”
Section: Figurecontrasting
confidence: 56%
“…The successful cryopreservation of IVP bovine embryos is essential to the establishment of its use on a commercial scale. With recent advances in freezing protocols, cryopreservation of IVP embryos has become a fast and reliable tool that allows the indefinite storage of embryos with higher potentials for in vitro development (Morató et al 2010). However, there has been little attention on the effects of antioxidants on the cryosurvival of vitrified-warmed embryos (Hosseini et al 2009).…”
Section: Introductionmentioning
confidence: 99%